BER-“SATU (Sistem Aplikasi Terintegrasi UMKM)” PERKUAT UMKM MENUJU INDONESIA MAJU - Zakia Mega Fatmala; Fadhilah Lanang; Iqlima Zahra (Politeknik Keuangan Negara STAN, 2022)
The Covid-19 pandemic was a non-natural national disaster that has hit the whole world, including Indonesia. The Covid-19 pandemic has resulted in problems not only in the health sector but also in the economic sector, especially the Micro, Small and Medium Enterprises (MSME) sector. MSMEs have an important role in absorbing Indonesian workers, but until now MSME actors are still having trouble getting business capital, as well as to conduct transactions with customers (customers). In addition, due to the Covid-19 pandemic, the income of MSME actors has decreased, due to the limited space for the community to carry out economic activities. This certainly affects Indonesia's economic growth, which is currently recovering due to Covid-19. Therefore, it is necessary to have a new system for MSMEs to facilitate their access to capital and transactions. With the SATU application, it is hoped that it can help the government help MSME actors from adversity due to Covid-19. The results of the effectiveness of the application can be seen from MSME actors, who are getting easier at getting business capital and making transactions easier. Thus, the income of MSME actors will increase, and the Indonesian economy could experience a significant recovery. In compiling this paper, the author uses a literature study research method.